Prevalence and Distribution of Human Papillomavirus Infection in Korean Women as Determined by Restriction Fragment Mass Polymorphism Assay - Lee, Eun Hee; Um, Tae Hyun; Chi, Hyun-Sook; Hong, Young-Joon; Cha, Young Joo (Journal of Korean medical science, 2012)
The development of a prophylactic vaccine that targets human papillomaviruses (HPV) 6, 11, 16, and 18 to prevent cervical cancer has increased interest in the ethnic and geographical distributions of HPV genotypes. We investigated HPV prevalence and type distribution by restriction fragment mass polymorphism (RFMP) testing a total of 60,775 specimens (aged 18-79 yr, median 44) taken from liquid-based cytology. Overall HPV positive rate of total patients was 34.2%. Among the positive patients, 87.7% was single type infections, and 12.3% was multiple HPV types. HPV-16 was the most prevalent genotype observed in 2,307 (26.0%), followed by type 52 in 2,269 (25.5%), type 58 in 1,090 (12.3%), type 18 in 633 (7.1%), type 56 in 436 (4.9%). The pattern of high risk-HPV positive rate according to age showed U-shape with a peak in HPV prevalence among women less than 30 yr of age, and a second peak among the older females aged 70 to 79 yr. The leading four high-risk HPV genotypes were HPV-16, HPV-52, HPV-58, and HPV-18 in descending order. In conclusion, this study provides the most representative prevalence and type-specific distribution of HPV among Korean women, and demonstrates that the epidemiology of HPV infection is different from that of other regions of the world.